1990
DOI: 10.1038/ki.1990.141
|View full text |Cite
|
Sign up to set email alerts
|

Intraglomerular platelet aggregation and experimental glomerulonephritis

Abstract: Oxygen free radical production inhibits ADPase-mediated antithrombotic action. Different forms of experimental glomerulonephritis (GN) are characterized by early glomerular influx of inflammatory cells and thrombus formation. The causal relationship of these inflammatory events is obscure. Previous studies have shown that glomerular ADPase in the rat kidney may function as a potent antithrombotic principle, whereas this enzyme is highly sensitive for oxygen free radicals. To study whether O2- producing inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…A second possibility is that the injected anti-Thy 1.1 antibody might induce glomerular leukocyte or platelet influx via increased release of chemoattractants or increases of the local procoagulant activity (48,49). Both leukocytes and platelets contain potent mesangial cell growth factors ( 1, 4).…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that the injected anti-Thy 1.1 antibody might induce glomerular leukocyte or platelet influx via increased release of chemoattractants or increases of the local procoagulant activity (48,49). Both leukocytes and platelets contain potent mesangial cell growth factors ( 1, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced generation of oxidants has been demonstrated in anti-Thy 1.1 and anti-GBM-induced glomerulonephritis with cytochemical techniques (12) and in isolated glomeruli (13) or macrophages (13,14). Several immune reactants, such as serumtreated zymosan (a C 3 b receptor stimulus), heat-aggregated IgG (an Fc receptor stimulus), immune complexes, complement components, and antinuclear antibody (15) all have been shown to trigger the oxidative burst.…”
Section: Role Of Oxidants In Leukocyte-dependent Glomerulonephritismentioning
confidence: 99%
“…Moreover, evaluation of DAB stainings revealed that the number of reactive oxygen species-producing cells was also increased in the livers of DOX-treated rats (Table 1). These DAB-positive cells consisted mainly of neutrophils, judged by the presence of polymorphic nuclei in these cells after evaluation of HE-stained liver sections and based on previous studies (Poelstra et al, 1990).…”
Section: Antifibrotic Potential Of Doxorubicin In Bdl Ratsmentioning
confidence: 99%
“…General toxicity was monitored by analysis of body weight (BW), whereas intrahepatic toxicity of DOX toward liver cells was examined by analysis of serum AST, ALT, AP, and ␥-GT levels. Inflammatory cell influx in the livers was assessed by diaminobenzidine (DAB) staining as described previously, as well as by evaluation of hematoxylin/eosin-stained liver sections (Poelstra et al, 1990;Greupink et al, 2005). To evaluate the effect of DOX on the bile duct epithelial cell proliferation, staining with a monoclonal antibody raised against cytokeratin 7 (Santa Cruz Biotechnology, Santa Cruz, CA) was performed, according to standard indirect immunohistochemical techniques.…”
Section: Antifibrotic Potential Of Doxorubicin In Bile Duct-ligated Ratsmentioning
confidence: 99%